Microwave Irradiation Enhances the Germination Rate of Tartary Buckwheat and Content of Some Compounds in Its Sprouts - Wang Shunmin; Wang Jianfei; Guo Yubao (Polish Journal of Food and Nutrition Sciences)
Tartary buckwheat (Fagopyrum tataricum) seeds were irradiated with microwaves at various power levels of 200, 400, 600 and 800 W for 10 or 30 s. The irradiated grains were germinated for 3, 5, and 7 days and harvested. The germination rate of the tartary buckwheat seeds and contents of some compounds in the sprouts were investigated. The results showed that the exposure to 600 W microwaves for 10 s resulted in the highest final germination rate after 7 days of germination, which was 2 times that of the control. The exposure of seeds to 800 W for 30 s showed the lowest germination rate (approximately 10%), which decreased by 87% compared with the control (p<0.05). The exposure at 600 W for 30 s stimulated the total flavones content, reduced the sugar and soluble protein contents, and increased the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. The highest free amino acid content (11 mg/g) was observed in 5-day sprouts exposed to 800 W for 10 s. Moreover, the microwave treatment had a positive effect on the catalase (CAT) and superoxide dismutase (SOD) activity.